Implementation of Marketing Strategy Through Social Media for Increase Quality as well as Engagement to Mr. Oluak - Iveren Monica; Suyono Saputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Mr Oluak is a food stall that provides dishes such as oysters and fried prawns covered in egg and flour. These dishes are inspired by Singaporean cuisine which is commonly known as Oluak / Fried Oyster. For the last 3 years the owner Mr. Oluak grows gradually, starting from product evaluation to employee training so that it can produce products that are more delicious and better known to the local and international community. Mr Oluak is located at HU Foodcourt , Batam Centre. One of the main problems faced if you don't have a strong brand and unique taste is the large number of competitors in the same field. With the increasing operational complexity of Mr. Oluak began to realize the importance of having a more structured and integrated marketing strategy. Therefore, it is hoped that the implementation of this marketing can help overcome existing problems.